Time-varying 3D optical torque via a single beam - Yi-Jing Wu; Jing-Han Zhuang; Pan-Pan Yu; Yi-Fan Liu; Zi-Qiang Wang; Yin-Mei Li; Cheng-Wei Qiu; Lei Gong (Nature Communications)
Abstract The spin angular momentum (SAM) plays a significant role in light-matter interactions. It is well known that light carrying SAM can exert optical torques on micro-objects and drive rotations, but 3D rotation around an arbitrary axis remains challenging. Here, we demonstrate full control of the 3D optical torque acting on a trapped microparticle by tailoring the vectorial SAM transfer. To this end, we construct a theoretical relationship between the 3D SAM vector of a tightly focused field and the local polarization helicity of the incident field. In practice, a single-beam configuration is proposed for dynamic 3D SAM manipulation, facilitating time-varying vectorial SAM transfer to particles. Control of 3D optical torque on birefringent microparticles is validated by simulations, and dynamic 3D rotations of optically trapped particles around arbitrary axes are experimentally demonstrated. Our work paves the way for manipulating 3D optical torque and particle spinning, which is expected to boost new functionalities and applications of optical tweezers.